Self‐assembled apatite on multiwalled carbon nanotubes substrates support osteogenic cell function. Issue 3 (7th October 2013) - Emohare, Osa; Rushton, Neil
Abstract The properties of multiwalled carbon nanotubes (MWCNT) make them attractive for use in biological matrices, especially in the development of bone‐like materials. However, their inherent hydrophobicity is a factor that has impeded broader use. A simple, novel method for coating MWCNT in apatite was developed and evaluated to enable their use in tissue engineering. This apatite coating was deposited on the nanotubes (which had been embedded in high‐density polyethylene) and facilitated the growth and differentiation of osteoblasts in a manner comparable to that of traditional tissue culture surfaces. Different levels of MWCNT purity (>90 and >95%) and chemical functionalization (carboxylation) were found to be amenable to deposition of an apatite coating and subsequent cell culture. The modalities evaluated were cell metabolic activity (MTS assay), cell proliferation (CyQuant assay), and cell differentiation (alkaline phosphatase assay); release of lactate dehydrogenase provided an indication of cytotoxicity. Although broadly comparable to traditional tissue culture surfaces, the carboxyl‐functionalized surfaces were associated with lower levels of growth and differentiation. The noncarboxylated surfaces proved to be broadly comparable to tissue culture plastic in terms of cell function. Therefore, apatite‐coated MWCNT provide a surface capable of supporting osteogenic cells. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 543–550, 2014.